P3HT/graphene composites synthesized using In situ GRIM methods. Issue 1 (15th September 2016) - Presto, Dillon; Song, Vivian; Boucher, David
ABSTRACT: Poly(3‐hexylthiophene)/graphene (P3HT/G) materials are synthesized using an in situ Grignard metathesis approach. The structural properties and spectroscopy of the materials are studied using NMR, FTIR, and UV–vis absorption spectroscopies, wide‐angle X‐ray scattering, atomic force microscopy and cyclic voltammetry. P3HT regioregularities ≥90% are observed in composites with approximate graphene compositions as high as 20% by weight. 1 H and 13 C NMR spectra of liquid phase dispersions reveal signals that are not observed in pristine P3HT. The intensity of these signals correlates with the graphene content, thereby indicating that the graphene is influencing the polymerization process. Anomalous features in the FTIR spectra of P3HT/G powders are also observed. AFM images of P3HT/G films show morphological differences between P3HT on graphene compared with P3HT domains on the silicon substrates. Cyclic voltammetry reveals a monotonic decrease in the energy of the HOMO and LUMO levels of P3HT with increasing graphene loading. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 60–76 Abstract : Poly(3‐hexylthiophene)/graphene (P3HT/G) materials are synthesized using an in situ Grignard metathesis approach. P3HT regioregularities between 90% and 96% are observed in composites with graphene compositions as high as 20% by weight. NMR and infrared absorption features in the composites are not observed in pure P3HT. Absorbance spectroscopy and cyclic voltammetry measurements of P3HT/G films reveal variations in the bandgap and the energies of HOMO and LUMO levels of P3HT that correlate with the graphene composition.